Removal of Chemazol Reactive Red 195 from aqueous solution by dehydrated beet pulp carbon - Dursun, Arzu Y.; Tepe, Ozlem (Elsevier, 2011)
An agricultural low-cost by-product, dehydrated beet pulp carbon (DBPC) was used as an adsorbent for removal of Chemazol Reactive Red 195 (CRR 195) from aqueous solution. The surface area of DBPC was measured as 9.5 m(2) g(-1) by using BET method. The results indicated that adsorption was strongly pH-dependent and optimum pH was determined as 1.0. The maximum dye adsorption capacity was obtained as 58.0 mg g(-1) at the temperature of 50 degrees C at this pH value. The Freundlich and Langmuir adsorption models were used for the mathematical description of the adsorption equilibrium and it was reported that, experimental data fitted very well to Freundlich model. Mass transfer and kinetic models were applied to the experimental data to examine the mechanisms of adsorption and potential rate-controlling steps. It was found that both external mass transfer and intra-particle diffusion played an important role in the adsorption mechanisms of dye and adsorption kinetics followed the pseudo-first-order type kinetic model. The thermodynamic parameters such as. Gibbs free energy changes (Delta G degrees), standard enthalpy change (Delta H degrees) and standard entropy change (Delta S degrees) had been determined. The results show that adsorption of CRR 195 on DBPC is endothermic and spontaneous in nature. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Dehydrated beet pulp carbon; Chemazol Reactive Red 195; Kinetics; Intraparticle diffusion model; External mass transfer model